me ajudem por favor???!!!!!
Anexos:
![](https://pt-static.z-dn.net/files/dec/a8eed9c2ecf90cc792c78805a8a86ea0.jpg)
Soluções para a tarefa
Respondido por
1
Resposta:
Explicação passo-a-passo:
a)
x + y = 3
x = 3 - y
Substituindo o x:
4x + y = - 3
4 (3 - y) + y = - 3
12 - 4y + y = - 3
- 3y = - 3 + 12
- 3y = 9
y = 9 ÷ (-3)
y = - 3
Para achar o x:
x = 3 - y
x = 3 - (- 3)
x = 6
Perguntas interessantes
Matemática,
8 meses atrás
Biologia,
8 meses atrás
Filosofia,
8 meses atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás
História,
1 ano atrás